Counterintelligence, Policy Recommendation and Military Convergence in Dealing with Current and Emerging Regional Implications of Jemaah Islamiyyah - Aslam, Mohd Mizan; Shuib, Shushil Azzam; Sayed Mahadi, Syed Abdul Razak (Islam Realitas: Journal of Islamic and Social Studies, 2023)
This study was conducted to seek reemerging threats of JI in recent years, counterintelligence taken by police and military convergence. Jemaah Islamiyah (JI) is an Islamist extremist group in Indonesia that seeks to overthrow the government and create a pan-Islamic state in Southeast Asia. It has ideological origins in the Darul Islam (DI) movement of the 1950s and 1960s, in which insurgents of West Javanese descent carried out a violent campaign that attempted to establish an Islamic state in Indonesia. Despite the arrest of more than 100 Jemaah Islamiyah (JI) members in the last two years, the militant organization appears resilient, partly due to its hierarchical organizational structure. Such a structure has enabled JI to have a strong agenda-setting capacity and exercise accountability and specialization within its hierarchy. This study is qualitative in nature. I conducted in-depth library and fieldwork research with former JI operatives and Police (POLRI & DENSUS 88, PDRM) officers. My findings show the survival patterns JI in the context of operations, which includes personal, political, economic, and community structure within their circle. To curb the threat of JI, I would like to suggest the Government of Indonesia and regional members devise an action plan to address the terrorist-related issues